Enhancing Critical Thinking Skills Through the TACK Model with Digital Flipbook Integration - Ridha Husnul Hayati; Muhamad Fahrur Rozi; Sari Febrianti; Rila Rahma Mulyani (AL-ISHLAH: Jurnal Pendidikan, 2025)
The rapid advancement of educational technology presents new opportunities to develop learning models that foster essential 21st-century skills, such as critical thinking. This study aims to develop a TACK (Technological, Andragogical, Content Knowledge) learning model utilizing a digital flipbook to enhance the critical thinking abilities of students in the Non-Formal Education (PNF) Department at Universitas Negeri Padang (UNP). This research follows a Research and Development (RD) design, encompassing five stages: needs analysis, model design, development, implementation, and evaluation. Data were gathered using pretest and posttest instruments to measure students’ critical thinking skills, alongside student satisfaction surveys to evaluate the model's reception. The findings indicate a significant improvement in students' critical thinking, with posttest scores (81.6) increasing by 25% from the pretest average (65.3). Additionally, the satisfaction survey revealed a 90% positive response rate, demonstrating strong student engagement and acceptance of the TACK model integrated with digital flipbook content. The TACK learning model, when supported by a digital flipbook, proves effective in enhancing students’ critical thinking skills within the context of non-formal education. Its adaptability suggests potential for broader application in both formal and informal educational settings. These results highlight the importance of integrating technological tools with pedagogical strategies to foster innovative and impactful learning experiences.